Quality of Jobs in the Philippines: Comparing Self-Employment with Wage Employment - Rana Hasan; Karl Robert L. Jandoc (Asian Development Bank (ADB), 2009)
Analysis of labor force survey data from 1994 to 2007 reveals that the structure of the Philippines labor force has been changing in several important ways. One is the movement from self-employment, the most predominant form of employment, to wage employment across a wide range of production sectors. How does one evaluate this change in terms of workers' earnings - arguably the most important element of job quality? Since labor force survey data do not provide information on earnings of the self-employed, we combine information on household incomes (disaggregated by source) from the Family Income and Expenditure Survey (FIES) with information on household members' employment-related activities from the Labor Force Survey (LFS) to shed light on this question. We also examine broad trends in the structure of employment, wages, and earnings. Our findings suggest that the decline of self-employment is no bad thing. For the most part, the earnings and educational profiles of the self-employed are very similar to those of casual wage earners, and clearly dominated by those of permanent wage earners even when observable worker characteristics are controlled for. An implication is that the self-employed do not seem to be "capitalists in waiting" as noted in recent literature. As selfemployment gives way to wage employment, especially casual wage employment in the services sector, the key challenge for policy is tackling the slow growth of wages and earnings indicated by both LFS and FIES data
hdl:11540/1800
Keywords: 330; Arbeitskräftepotenzial; Selbstständige; Arbeitskräfte; Philippinen